2023
DOI: 10.1021/acsomega.2c08243
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Rheological Behavior, and pH Responsiveness of CTAB/HCl Acidic Emulsion: Experimental Investigation

Abstract: Cetyltrimethylammonium bromide (CTAB) surfactant was proven to be a reliable emulsifier for creating stable emulsions used for drilling, well stimulation, and EOR. The presence of acids like HCl during such operations may lead to the formation of acidic emulsions. No previous comprehensive investigations have been done to study the performance of CTAB-based acidic emulsions. This paper, therefore, presents experimental investigations of the stability, rheological behavior, and pH responsiveness of a CTAB/HCl-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Mohyaldinn et al previously studied the stability, rheological behaviour, and pH responsiveness of the CTAB/HCl acidic emulsion, and showed that the CTAB-based emulsion destabilised at a higher pH (10), and demulsified within 60 min. 41 Additionally, after the injection of HCl (pH 6.16), the surfactant molecules regain their surface active nature and adsorbed onto the surface of the nanoparticles which made them hydrophobic. This caused the reformation of a stable Pickering emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…Mohyaldinn et al previously studied the stability, rheological behaviour, and pH responsiveness of the CTAB/HCl acidic emulsion, and showed that the CTAB-based emulsion destabilised at a higher pH (10), and demulsified within 60 min. 41 Additionally, after the injection of HCl (pH 6.16), the surfactant molecules regain their surface active nature and adsorbed onto the surface of the nanoparticles which made them hydrophobic. This caused the reformation of a stable Pickering emulsion.…”
Section: Resultsmentioning
confidence: 99%